Características sociodemográficas, sintomas de ansiedade e depressão, fissura e motivação para mudança em dependentes de crack em tratamento - Soares, Iracil Rosinda Pires (Universidade do Vale do Rio dos Sinos, 2014)
Substance dependence is recognized as one of the most serious and complex public health problems worldwide. The need to develop treatment is essential and must take into account the differences between sexes when concerning depression and anxiety, motivation to change problem behavior and craving for crack. To this end, it is essential to identify the characteristics and specificities of the chemically dependent in order to develop effective prevention and intervention measures. This dissertation is organized in two empirical articles. The first article presents the results of the demographic profile of men and women addicted to crack hospitalized for detoxification in public and private health systems. Participated 159 adults (80 men and 79 women), aged between 18 and 60 years, mean age of 30.7 years (SD=8.54). Of the participants, 99 (62.3%) were hospitalized in two public institutions, and 60 (37.7%) in a private institution located in Porto Alegre, RS, Brazil. The average age for the first situation of crack consumption was 24 years (SD=8.6). The instruments used were a sociodemographic interview and pattern of psychoactive substance use and the Mini International Neuropsychiatric Interview (M.I.N.I. Plus). The results identified, in the present study, vulnerabilities in both sexes and at both institutions in the following variables: education, family income, diagnosed diseases, use of licit and/or illicit drugs in the family, reasons for crack consumption, frequency of consumption of crack rocks at the beginning of use and before hospitalization, resources for obtaining crack, treatment settings (rehabilitation centers, inpatient settings), criminal prosecution and offense. The data indicate the importance of knowing the profile of the crack dependent for this can contribute to the planning of preventive programs regarding the use and abuse of psychoactive substances. The second empirical article aimed to verify the anxiety and depression symptoms, assess the craving for crack and identify the motivation for behavior change, characterizing the differences between male and female crack dependent adults admitted for detoxification in public and private institutions. The instruments used were the Beck Anxiety Inventory (BAI), Beck Depression Inventory (BDI-II), Cocaine Craving Questionnaire-Brief (CCQ-B) for Crack, Scale URICA (University of Rhode Island Change Assessment) and The Readiness-to-Change ruler. According to the results, the sample (N=159) presented moderate symptoms of anxiety; minimal symptoms of depression; moderate craving for crack; it was found on the stage of contemplation and action regarding the motivation to change the addictive behavior, however, when the score of readiness to change was inquired, the sample was unmotivated 18 regarding behavior change, whereas The Readiness-to-Change ruler showed willingness to change and confidence to achieve change. We observed a higher frequency of severe cases of anxiety in the public system and increased frequency of women with severe anxiety in the public system. It was verified that the main predictors of readiness to change (RTC) were in relation to sex, female; the place of addmition, private institution; and who have not experienced significant losses throughout life. These findings suggest that sex plays an important role in chemical dependency, since they showed statistically significant differences with respect to anxiety and motivation to change behavior. These results confirm the need for more research involving investigative issues between male and female in crack dependence and other psychoactive substances.
Keywords: Dependência de crack; Perfil; Ansiedade; Depressão; Fissura; Motivação para mudança; Homens; Mulheres; Psicologia; Addiction to crack; Profile; Anxiety; Depression; Cravings; Motivation to change; Men; Women; Psychology; ACCNPQ::Ciências Humanas::Psicologia